2019
DOI: 10.1016/j.jmmm.2019.04.088
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of ferromagnetism in (In,Fe)Sb diluted magnetic semiconductor to variation of charge carrier concentration

Abstract: The influence of He + ion irradiation on the transport and magnetic properties of epitaxial layers of a diluted magnetic semiconductor (DMS) (In,Fe)Sb, a two-phase (In,Fe)Sb composite and a nominally undoped InSb semiconductor has been investigated. In all layers, a conductivity type conversion from the initial n-type to the ptype has been found. The ion fluence at which the conversion occurs depends on the Fe concentration in the InSb matrix. Magnetotransport properties of the two-phase (In,Fe)Sb layer are st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In [8,11] it was assumed that the ferromagnetism of (III,Fe)V DMSs (in particular in (Al,Fe)Sb and (In,Fe)Sb) is associated with the ferromagnetic coupling between the second nearest neighbor Fe atoms via the superexchange interaction. In [12] we revealed a weak interrelation between the ferromagnetism and the charge carrier concentration in (In,Fe)Sb that is fundamentally different from Mndoped III-V DMS.…”
Section: Introductionmentioning
confidence: 84%
“…In [8,11] it was assumed that the ferromagnetism of (III,Fe)V DMSs (in particular in (Al,Fe)Sb and (In,Fe)Sb) is associated with the ferromagnetic coupling between the second nearest neighbor Fe atoms via the superexchange interaction. In [12] we revealed a weak interrelation between the ferromagnetism and the charge carrier concentration in (In,Fe)Sb that is fundamentally different from Mndoped III-V DMS.…”
Section: Introductionmentioning
confidence: 84%
“…Second, ferromagnetism with T C = 40 K was also reported for insulating (Al,Fe)Sb, whose carrier concentration was 3 × 10 17 cm −3 , three to four orders of magnitude smaller than that of (Ga,Mn)As [9]. Third, it was recently shown that the ferromagnetism of (In,Fe)Sb is not significantly influenced by carrier concentration and even by carrier type [33].…”
Section: Discussionmentioning
confidence: 84%
“…Compounds of the III–V semiconductor family have been widely used in different electronic and optoelectronic devices, such as heterostructure bipolar transistors, diode lasers, photodetectors, and electro-optic modulators, among others. Also, these compounds are promising candidates for solar water splitting, , offering remarkable photon-to-electron energy conversion rates higher in comparison with the silicon-based system . Also, several studies have been carried out impurifying the surface with magnetic materials (Fe, Co, Ni, Mn) to form the so-called diluted magnetic semiconductors (DMS). …”
Section: Introductionmentioning
confidence: 99%